CHARACTERISTICS OF APHORISMS RELATED TO THE CONCEPT OF "LOVE" (American Journal of Pedagogical and Educational Research, 2023)
This article deals with the lexical-semantic analysis, national-cultural features of one of the scientific fields of linguistics, paremiology, inparticular, aphorisms related to the concept of "love".